Differential Gene Expression in Menstrual Endometrium From Women With Self-Reported Heavy Menstrual Bleeding. (January 2017) - Girling, Jane E.; Lockhart, Michelle G.; Olshansky, Moshe; Paiva, Premila; Woodrow, Nicole; Marino, Jennifer L.; Hickey, Martha; Rogers, Peter A. W.
Heavy menstrual bleeding (HMB) is a significant social and public health issue for menstruating women. Development of targeted treatments has been limited by poor understanding of local mechanisms underlying HMB. We aimed to determine how gene expression differs in menstrual phase endometrium from women with HMB. Menstrual phase endometrial biopsies were collected from women with (n = 7) and without (n = 10) HMB (regular menstrual cycles, no known pelvic pathology), as well as women with uterine fibroids (n = 7, n = 4 had HMB). Biopsies were analyzed using Illumina Sentrix Human HT12 arrays and data analyzed using "Remove Unwanted Variation-inverse". Ingenuity Pathway Analysis and the Database for Annotation, Visualization and Integrated Discovery v6.7 were used to identify gene pathways, functional gene clusters, and upstream regulators specific to the clinical groupings. Individual genes of interest were examined using quantitative polymerase chain reaction. In total, 829 genes were differentially expressed in one or more comparisons. Significant canonical pathways and gene clusters enriched in controls relative to both HMB and fibroid groups suggest the mechanisms responsible for HMB include modifications of the endometrial inflammatory or infection response. In contrast, differentially expressed genes in women with fibroids suggest modifications of hemoglobin, antigen processing, and the major histocompatibility complex (class II, beta chain) activity. In conclusion, HMB associated with fibroids may be regulated by different endometrial mechanisms from HMB in women without fibroids and from normal menstrual bleeding. These novel data provide numerous testable hypotheses that will advance our understanding of the mechanisms responsible for HMB.